Antecedents of and Their Impact on Purchase Intention of Customers Purchasing through Social Media: An Empirical Research on Facebook in Bangladesh - Barnali Nandi; Mohammad Rakiv (Universitas Airlangga, 2020)
This research paper aims to clarify the relationship between the influential factors and their impact on the intention of the customers to make a purchase from social media particularly Facebook in Bangladesh.From the literature review, a conceptual model has been established, which is followed by the multiple regression model.The collected data are analyzed using multiple regression analysis. Among the four independent variables three factors namely trust, perceived value and brand loyalty are founded to be influential at the 0.05 significance level and the remaining variable perceived risk has some impact on the purchase intention of the customers using social media but it is not as much influence as other three factors at this significance level.Although there are some researchers conducted to measure the impact of social media marketing, there is a rare study in the context of emerging economies like Bangladesh that tries to investigate the influential factors which ultimately drive customers to make purchases from Facebook pages in Bangladesh.This research proves to be helpful for retailers who are doing their marketing using social platforms in Bangladesh. As most of the people in Bangladesh are using Facebook, this study helps the retailers to understand which factors ultimately drive customers to make a purchase from the Facebook pages in Bangladesh.